Effectiveness of Implementing Trauma Healing on Students' Learning Motivation Post-Earthquake - Sar'an, Sar'an; Fadlan, Amul Husni; Fuadi, Afif; Hartini, Sri (Al-Kahfi: Jurnal Pendidikan Agama Islam, 2026)
Trauma is a life experience that disrupts the biochemical balance of the brain's psychological information processing system. Trauma is caused by various cruel things that befall a person and deeply imprint their memory. To eliminate it, recovery efforts are carried out. These efforts are often termed trauma healing. The purpose of this study was to determine the effectiveness of trauma healing in dealing with trauma experienced by children aged 18 years in the area closest to the West Pasaman earthquake. The method used in this study was the Action Research Method, a research method used to test, develop, discover, and create new actions. So that when these actions are applied in work, the work process will be easier, faster, and produce more and quality results. In this study, the researcher directly acted as the trauma healing actor from planning to implementation. The results of this study showed that the trauma healing program in schools made children cheerful and more enthusiastic about going to school, studying, and worship. During the post-earthquake period, school learning was carried out in groups during the day, while in the morning, learning and trauma healing were carried out at school.